Train-the-Trainer Evaluation of Technology-Enhanced Learning in Preservice Midwifery Education in Nigeria: Qualitative Descriptive Study - Isabella Garti; Nadyen Shikpup; Ophelia Tonto; Michelle Gray; Halima Musa Abdul; Awwal Mohammed Ladan (JMIR Nursing, 2026)
Abstract Background Midwifery education in Nigeria is undergoing a transformation in pedagogical approach. Existing traditional teaching materials are being supplemented by digital technology-enhanced learning resources; however, educators’ limited pedagogical capacity may hinder their adoption. Thus, train-the-trainer (TTT) workshops were implemented to build capacity among midwifery educators to prepare them for the implementation of a digital learning platform across 20 institutions in Nigeria. Objective This study aimed to describe the development and qualitative evaluation of a TTT program to support the implementation of a technology-enhanced learning platform within preservice midwifery education in Nigeria. We aimed to evaluate participants’ perceptions of the training and their preparedness to implement their learning. Methods The workshop was developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. A 3-day TTT program was delivered in 2 cohorts in July 2025 to a purposive sample of 80 institution-nominated midwifery educators and information and communication technology officers from 20 pilot institutions. A qualitative descriptive study was conducted to explore participants’ perceptions of the training and their readiness to implement and support the technology-enhanced learning platform within their institutions. Data were analyzed using qualitative content analysis. Results Pre-workshop responses demonstrated varying levels of prior exposure to and use of digital technologies, as well as differing expectations of the training. Four themes emerged from the post-workshop evaluation. Participants perceived improvements in their understanding of pedagogical and technology-enhanced learning approaches; reported greater readiness to support implementation and knowledge transfer within their institutions; highlighted infrastructure and technical support barriers to implementation; and emphasized the need for ongoing capacity building, monitoring, and support to promote long-term sustainability. Conclusions Rather than evaluating educational outcomes, this study provides early evidence of educator readiness, implementation considerations, and sustainability requirements for technology-enhanced learning in preservice midwifery education in low-resourced settings such as Nigeria. A multifaceted approach combining capacity building, ongoing support, technical requirements, and institutional commitment to continuous improvement is needed. Future phases of this implementation research will evaluate educational, implementation, and institutional outcomes associated with the digital learning platform.